1997
DOI: 10.1200/jco.1997.15.11.3363
|View full text |Cite
|
Sign up to set email alerts
|

High-titer HER-2/neu protein-specific antibody can be detected in patients with early-stage breast cancer.

Abstract: The presence of HER-2/neu antibodies in breast cancer patients and the correlation with HER-2/neu-positive cancer implies that immunity to HER-2/neu develops as a result of exposure of patients to HER-2/neu protein expressed by their own cancer. These findings should stimulate further studies to develop the detection of immunity to oncogenic proteins as tumor markers, as well as the development and testing of vaccine strategies to induce and augment immunity to HER-2/neu for the treatment of breast cancer or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
203
0
2

Year Published

1998
1998
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(211 citation statements)
references
References 11 publications
6
203
0
2
Order By: Relevance
“…It is noteworthy that in our study one of 29 human control sera harbored speci®c anti-ErbB2 reactivity. Sporadic anti-ErbB2 immunoreactivity in apparently normal donors was also observed by others (Disis et al, 1994a(Disis et al, , 1997. In the absence of detailed clinical information on normal donors, the reason for such reactivity is currently unknown.…”
Section: Discussionmentioning
confidence: 65%
“…It is noteworthy that in our study one of 29 human control sera harbored speci®c anti-ErbB2 reactivity. Sporadic anti-ErbB2 immunoreactivity in apparently normal donors was also observed by others (Disis et al, 1994a(Disis et al, , 1997. In the absence of detailed clinical information on normal donors, the reason for such reactivity is currently unknown.…”
Section: Discussionmentioning
confidence: 65%
“…Thus, we next compared the abilities of our DC populations to stimulate primary MLRs against allogeneic CD8 + T cells. We found that DC HER -2 / TNF -a , which had been coinfected with AdVHER2 / neu and AdVTNF -A, induced stronger DCs were infected with either AdVGFP or AdVTNF -a at MOI of 100 ( 1Â10 7 DCs vs 1Â10 9 pfu of either AdVGFP or AdVTNF -a ), or both of these two adenoviruses at MOI of 100 for each adenovirus ( 1Â10 7 DCs vs 1Â10 9 pfu of AdVGFP and 1Â10 9 pfu of AdVTNF -a ). The infected DCs were stained by PE -conjugated anti -TNF -a antibody as described under Materials and methods.…”
Section: Her -2 / Tnf -A Cells Induce Enhanced T -Cell Proliferatimentioning
confidence: 91%
“…12,36 -43 For example, anti-p53 antibodies were detected in 3-65% of sera of patients with cancer, 38,39 and anti-HER2/neu antibodies were detected in 11% of patients with breast carcinoma. 40 Also, antibodies reactive with cancer/testis antigen, such as MAGE, GAGE, BAGE, SSX, and NY-ESO-1, were found in 4.2-12.5% of sera of patients with melanoma and carcinoma of the lung, breast, and ovary. 41,42 Antibodies against mucins were elicited in 8.3% of patients with various types of cancer.…”
Section: Anti-m2bp Antibody In Sera From Patients With Lung Carcinomamentioning
confidence: 97%